Pilocytic astrocytoma with spontaneous malignant transformation with intracranial and skeletal dissemination: case report and review of the literature. (2nd January 2022) - Konar, Subhas K.; Nandeesh, B. N.; Sandhya, M.; Chandana, N.; Devi, B. Indira; Bhat, Dhananjaya I.
Abstract: Pilocytic astrocytoma is a benign low-grade tumor with a favorable prognosis. We present a 47-year-old- lady with a posterior fossa pilocytic astrocytoma who underwent surgical decompression. She developed multiple early local recurrences Along with malignant transformation of the cranial lesion she developed skeletal dissemination within a very short time frame. There were no features or family history of neurofibromatosis 1. She did not receive radiotherapy or chemotherapy prior to the recurrences.